A computational study on the nature of meso‐β scale vortex coalescence in a tropical atmosphere. (9th June 2017) - Schecter, David A.
Abstract: Tropical weather systems commonly contain a variety of mesoscale vortices whose interactions may influence the timing of tropical cyclone formation. Previous computational studies have found that interactions ending in coalescence can either help or hinder development depending on the specific circumstances. Despite the potential importance of mesoscale vortex merger, complications introduced by baroclinic effects and diabatic processes have impeded progress toward elucidating its mechanics. The present study is an effort to advance current understanding by way of idealized numerical experiments with a cloud‐permitting model. Direct comparisons are made between dry adiabatic and moist diabatic simulations of meso‐β (20–200 km) scale vortex merger on a tropical oceanic f‐plane. Consistent with a number of earlier studies, deep cumulus convection is found to accelerate the late stage of surface‐concentrated vortex merger over a warm ocean. On the other hand, incorporating artificial radiation and cloud processes into the numerical model substantially hinders the merger of middle‐tropospheric vortices over a moderately cooler ocean. Such hindering coincides with the partial suppression of shear‐induced vortex misalignments whose amplifications and rotations appear to be essential to the dry adiabatic merger mechanism. The aforementioned dry merger mechanism is examined in detail. Irrotational winds linked to the horizontal divergence field are found to largely control the system‐centric influx of absolute vorticity, in sharp contrast to ideal two‐dimensional hydrodynamics. The consequences of lowering (raising) the sea‐surface temperature under the moist surface‐concentrated (middle‐tropospheric) system are briefly addressed. Key Points: The mechanisms of meso‐ β scale vortex merger are diverse Diabatic processes in a cloud resolving model can either help or hinder merger Irrotational winds can be important in driving the system‐centric influx of vorticity during merger in a dry adiabatic system